The Right to Equality in the South African Constitution - O'Regan, Kate (Columbia Journal of Gender and Law, 2013)
When the young Frenchman, Alexis de Tocqueville, visited the United States of America in the early 1830s, he was fascinated by the idea of democracy and the role of law and lawyers within it. He went to America dismayed by the weak state of democracy in Europe and in France, in particular, in order to observe how democracy was faring in the United States of America. One of his observations was that lawyers had an important role to play in the development of a democracy. “I should like to get this matter clear,” he wrote, “for it may be the lawyers are called on to play the leading part in the political society which is striving to be born.”‘ If one considers De Tocqueville’s remarks in relation to the question of gender equality, there can be little doubt that Justice Ruth Bader Ginsburg has been a lawyer who, in the different roles she has played as a lawyer, a professor, and a judge, has played the leading part in the legal struggle for gender equality and it is a great honour to have been invited to participate in this symposium today in her honour.